1989
DOI: 10.1136/adc.64.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril for severe heart failure in infancy.

Abstract: SUMMARY Eight infants aged between 4 days and 12 weeks with severe heart failure that was refractory to optimal conventional treatment with diuretics were treated with enalapril. The starting dose was 0-1 mg/kg/day, increasing according to response to 0 12-O-43 mg/kg/day. One infant with severe myocarditis did not tolerate enalapril because of hypotension and later died of intractable heart failure. Six of the remaining patients had congenital systemic to pulmonary shunts and one had a simple aortic coarctatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 11 publications
(3 reference statements)
0
21
0
Order By: Relevance
“…enalapril. Other adverse effects included hyperkalemia (>5 mmol/ Frenneaux et al [66] reported one neonate with myocarditis who L) in four patients, three of whom were receiving simultaneous was treated with enalapril and developed hypotension; the patient spironolactone. Hyperkalemia was quickly normalized by disconlater died of intractable heart failure.…”
Section: Renal Effects 42 Hypotensionmentioning
confidence: 96%
See 2 more Smart Citations
“…enalapril. Other adverse effects included hyperkalemia (>5 mmol/ Frenneaux et al [66] reported one neonate with myocarditis who L) in four patients, three of whom were receiving simultaneous was treated with enalapril and developed hypotension; the patient spironolactone. Hyperkalemia was quickly normalized by disconlater died of intractable heart failure.…”
Section: Renal Effects 42 Hypotensionmentioning
confidence: 96%
“…Frenneaux et al [66] treated six infants with a large ventricular inhibitors in chronic heart failure result not only from hemodyseptal defect and heart failure with enalapril, with clinical imnamic effects, but from the prevention of harmful myocardial and provement noted in all patients. The mean weight of the patients vascular remodeling resulting from the renin-angiotensin-aldosterincreased from 3.3 to 3.6kg after 2 weeks of treatment with one system.…”
Section: Ace Inhibitors Suggesting That the Beneficial Effects Of Acementioning
confidence: 97%
See 1 more Smart Citation
“…However, its use in pediatrics has been poorly evaluated for this indication (Eronen et al, 1991;Frenneaux et al, 1989;Lloyd et al, 1989;Rheuban et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…A few non-randomised studies have demonstrated haemodynamic improvement with angiotensin-converting enzyme inhibitors (ACEIs) in paediatric patients, such that ACEIs have gained widespread acceptance for use with diuretics 13. Initiation of captopril requires inpatient monitoring due to hypotension and impairment of renal function.…”
mentioning
confidence: 99%